Poor second ovarian stimulation in cynomolgus monkeys (Macaca fascicularis) is associated with the production of antibodies against human follicle-stimulating hormone - Yasunari SEITA; Chizuru IWATANI; Hideaki TSUCHIYA; Shinichiro NAKAMURA; Fuminori KIMURA; Takashi MURAKAMI; Masatsugu EMA (The Society for Reproduction and Development, 2019)
Cynomolgus monkeys (Macaca fascicularis) are a valuable model organism for human disease modeling because human physiology and pathology are closer to those of cynomolgus monkeys than rodents. It has been widely reported that mature oocytes can be recovered from cynomolgus monkeys through ovarian stimulation by human follicle-stimulating hormone (hFSH). However, it is unknown whether mature oocytes can be effectively obtained through a second ovarian stimulation by hFSH. Here, we report that some ovaries (eight ovaries from 14 female monkeys) were stimulated effectively by hFSH even after the first ovum pick up, whereas the others were stimulated poorly by hFSH. Furthermore, we found antibodies against hFSH only in the serum of female monkeys with poorly stimulated ovaries. Collectively, these data suggest that anti-hFSH antibodies in serum may cause a poor ovarian response to hFSH stimulation. Finally, detection of such antibodies as well as observation of the ovary over the course of hFSH administration might be useful to predict favorable second ovarian stimulation by hFSH.